Student Perceptions of Talent and Interest Mapping Learning Media Based on RIASEC - Yuniarni, Desni; Putri, Amallia (Buletin Konseling Inovatif, 2025)
The main purpose of this study is to find out how students perceive the learning media provided during lectures. Learning media is one of the most important tools in learning. Less interesting learning media will make students not interested in learning. This research takes the form of a qualitative case study using face-to-face interviews and administering questionnaires with participants, as data collection tools. The subjects of the research are 67 students in semesters V and VII in the Guidance and Counseling Study Program. The sampling technique used is purposive sampling. The results of the study show that students' perception of the media that has been used in the RIASEC-based interest, talent and character mapping course is a learning media that is not interesting, less varied, tends to be boring, such as the use of PowerPoint. Students' perception of the media that should be used for the course is a learning medium that can attract students' interest in learning, such as the use of multimethod and interactive multimedia, e-books that contain examples of the application of important and more detailed materials.